The Analysis of Organizational Changes using Structural Equation Modelling with Mediating Readiness to Change in Higher Education - Rindang Ayu; Nurul-Azza Abdullah; Wan Shahrazad Wan Sulaiman; Mohd Nasir Bin Selamat (Society of Visual Informatics, 2023)
This research study demonstrates that the readiness to change moderates the association between supervisor support and commitment to organizational change. The variable